Berlitz Latin American Spanish CD pack (Berlitz / APA, 2003)
This audio CD provides for learning conversational skills one can use while travelling abroad. Its dialogues feature over 300 essential expressions. The phrase book includes more than 1,200 useful words and phrases, travel tips, dictionary and pronunciation guide.